Lack of Efficacy of Drug Therapy in Preventing Takotsubo Cardiomyopathy Recurrence: A Meta‐analysis. Issue 7 (3rd April 2014) - Santoro, Francesco; Ieva, Riccardo; Musaico, Francesco; Ferraretti, Armando; Triggiani, Giuseppe; Tarantino, Nicola; Biase, Matteo Di; Brunetti, Natale Daniele
Abstract Background Efficacy of chronic drug therapy in prevention of stress‐induced cardiomyopathy recurrences is not well established. We therefore aimed to evaluate in this meta‐analysis whether pharmacological treatment can effectively prevent takotsubo cardiomyopathy (TTC) recurrences, according to available studies. Hypothesis There is no evidence for preventing TTC recurrence by drug therapy. Methods After a PubMed search, we conducted a meta‐analysis of available studies (clinical nonrandomized registries) on efficacy of drug therapy in preventing recurrence of TTC. Results A total of 23 (4.5%) TTC recurrences occurred in the 511 patients included in the analysis. Seven studies on the effects of β‐blockers on prevention of TTC recurrence were evaluated; the odds ratio (OR) was 0.44 and the 95% confidence interval (CI) was 0.15‐1.31. In 5 studies on the effects of angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers, the OR was 0.42 and the 95% CI was 0.08‐2.36; in 3 studies on statins, the OR was 0.74 and the 95% CI was 0.07‐7.3; and in 4 studies on aspirin, the OR was 0.33 with a 95% CI of 0.05‐2.17 (P value not significant in all cases). Conclusions A meta‐analysis of the efficacy of different medications through the clinical TTC registries available showed no clinical evidence for a standard drug treatment in the chronic management of TTC. β‐Blockers, angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers, statins, and aspirin do not seem to significantly reduce recurrences of TTC. Randomized, adequately powered studies are needed to further assess this issue.